Effect of Flow Attack Angle for V-Wavy Plate on Flow and Heat Transfer in a Square Channel Heat Exchanger - Amnart Boonloi; Withada Jedsadaratanachai (Journal of Engineering)
Effects of flow attack angles of the V-wavy plate on flow and heat transfer in a square channel heat exchanger are investigated numerically. The V-wavy plates with V-tips pointing downstream and upstream called V-Downstream and V-Upstream, respectively, are examined for the Reynolds number in the range of 3000–10,000. The finite volume method with SIMPLE algorithm is selected to solve the present problem. The numerical results are presented in terms of flow and heat transfer visualization. The thermal performance analysis is also concluded in the form of Nusselt number ratio (Nu/Nu0), friction factor ratio (f/f0), and thermal enhancement factor (TEF). The numerical result shows that the wavy plate can induce the swirling flow through the test section for all cases. The swirling flow disturbs the thermal boundary layer on the channel wall which is the reason for heat transfer enhancement. In range studies, the heat transfer rate increases around 3–6.5 and 2.8–6 times above the smooth channel for V-Downstream and V-Upstream, respectively. The optimum TEF is found at α = 20° and Re = 3000 to be around 2.09 for V-Upstream case.